Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Flapping motion configurations of geomagnetotail current sheet - Peng Shao; Chao Shen; Yonghui Ma; Zhaojin Rong; Yufei Zhou; Chi Zhang; M. Dunlop; Yong Ji (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Effect of in planta phosphorus on aluminum-induced inhibition of root elongation in wheat - Ji Feng Shao; Jing Che; Rong Fu Chen; Jian Feng Ma; Ren Fang Shen (Plant and Soil, 2015)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Nicotianamine synthase gene family as central components in heavy metal and phytohormone response in maize - Mei-Liang Zhou; Lei-Peng Qi; Jun-Feng Pang; Qian Zhang; Zhi Lei; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Aldehyde dehydrogenase protein superfamily in maize - Mei-Liang Zhou; Qian Zhang; Ming Zhou; Lei-Peng Qi; Xiong-Bang Yang; Kai-Xuan Zhang; Jun-Feng Pang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Functional & Integrative Genomics, 2012)

Cloning, Characterization and Functional Analysis of a Phenylalanine Ammonia-lyase Gene (FtPAL) from Fagopyrum tataricum Gaertn - Cheng Lei Li; Yue Chen Bai; Hui Chen; Hai Xia Zhao; Ji Rong Shao; Qi Wu (Plant Molecular Biology Reporter, 2012)

Genetic diversity of four new species related to southwestern Sichuan buckwheats as revealed by karyotype, ISSR and allozyme characterization - Mei-Liang Zhou; Da-Quan Bai; Yu Tang; Xue-Mei Zhu; Ji-Rong Shao (Plant Systematics and Evolution, 2012)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Karyotype and genetic relationship based on RAPD markers of six wild buckwheat species (Fagopyrum spp.) from southwest of China - Xiao-yan Yang; Zhen-Fang Wu; Hui Chen; Ji-rong Shao; Qi Wu (Genetic Resources and Crop Evolution, 2010)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)